Early child Cantonese facts and implications - Tse, Shek Kam 1948-; Li, Hui 1968- (de Gruyter Mouton, 2011)
This book will be the first publication on record that systematically and comprehensively addresses the acquisition and development of Cantonese in early childhood. It draws upon evidence from up-to-date reviews of associated literature, on the outcomes of numerous research studies conducted by the authors and on the outcomes of an in-depth study of the largest corpus of early childhood Cantonese. To supplement and illuminate published trends in the literature, carefully gathered reliable and valid empirical data will be critically scrutinized. The evidence will be used to clarify and examine theoretical assumptions and to outline putative developmental trends in early childhood Cantonese pragmatics. Shek Kam Tse, University of Hong Kong, China; Hui Li, University of Hong Kong, China
Keywords: Spracherwerb; Kantonesisch